(untitled) (Salud, Arte y Cuidado, 2018)
The objective of this study was to determine the accompaniment of the family group patients with diseases in terminal stage in environments home and hospital for a good death. This research is located in the quantitative, positivist paradigm, not experimental, descriptive type supported by field, cross design. The population under study was 13 relatives; which were with a medical diagnosis of Cancer in terminal phase of his illness, who informed consent is applied to an instrument of 24 items, results reflect that the accompaniment of the family group to patients with end-stage diseases is focused on willingness to care which indicate that the family must have the time needed to provide care to his patient and help channel the wishes of the patient to help you navigate your last days of life and that the family feels in the ability to provide the care necessary your family member in your home, in relation to the recognition of the spiritual needs the family should bow to any belief as a method of coping to disease, likewise, that the religious beliefs that the patient has influence on the way in which is facing the situation of his illness. On the other hand, the demonstrations of affection the family shows expressions of weeping and despair so he can see how much want it, the sick person prefers to be at his home during the last days of her life under the care of relatives, and the handling of the emotions of the patient are anger, sadness and fear experienced during the illness.